THE RESEARCH’S TREND OF ECONOMIC GROWTH IN THE DEVELOPING COUNTRY IN THE LAST FIVE YEARS - Rafsanjani, Mohamad Arief; Subroto, Waspodo Tjipto; Sakti, Norida Canda; Srisuk, Prattana (Universitas Tanjungpura, 2025)
Economic growth in developing countries is vital for alleviating poverty, reducing inequality, and fostering sustainable development. However, this field faces challenges such as resource constraints and global disruptions, including the COVID-19 pandemic. This study uses bibliometric methods to analyze research trends on economic growth in developing countries over the past five years (2020–2024). Based on 232 publications indexed in the Scopus database, we employed the bibliometric analysis using scival tools provided by Elsevier to examine publication metrics, citation counts, and thematic patterns. The results show a steady rise in research output, with a focus on sustainability and environmental economics. China leads in both scholarly output and citation impact, followed by contributions from the United States and Pakistan. Key topics include the Environmental Kuznets Curve, renewable energy, and trade liberalization, aligning with global sustainability goals. However, research from regions like Africa and Latin America remains underrepresented, and emerging areas such as digital transformation and equitable growth receive limited attention. These findings emphasize the need to design policies that balance economic growth with environmental sustainability. Enhancing regional collaboration and supporting underrepresented areas can improve research equity and impact. This study provides actionable insights and identifies opportunities for more inclusive and impactful future research in economic growth.